EFFECT OF COMPENSATION, ORGANIZATIONAL CULTURE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE ON THE INSPECTORATE OF THE MINISTRY OF COOPERATIVES AND SMES - Zaman Zaini; Budiyanto (Journal Indonesia Law and Policy Review, 2021)
The purpose of this study was to determine the extent of the influence of compensation, organizational culture and work discipline on employee performance at the Inspectorate of the Ministry of Cooperatives and SMEs. The analysis used is descriptive quantitative and inferential statistics with correlation analysis and multiple linear regressions. The research population was conducted on employees with a sample of 42 people. The sampling technique used is proportional random sampling technique. While the data collection technique was carried out using a direct survey using questionnaires and hypotheses instruments. This study was tested using multiple regression analysis using the SPSS version 23.0 program. Hypothesis testing using multiple linear regression analysis with the regression equation: Y = 82.704 + 0.752X1 + 0.993X2 + 0.344X3. The results of the F test show the results of Fcount (61.217) > Ftable (2.83), the influence of compensation, organizational culture and work discipline variables together on employee performance. The results of the t-test show the value of tcount (3.547) > ttable (2.018) for compensation, tcount (6.873) > ttable (2.018) for organizational culture, tcount (2.393) > ttable (2.018) for work discipline, meaning that there is an effect of compensation, organizational culture and work discipline on employee performance. The results of the coefficient of determination show that compensation, organizational culture and work discipline variables are able to contribute to employee performance by 0.927 or 92.7% while the remaining 7.3% is influenced by other variables outside the variables studied.